Application of Adaptive Structure based on Natural Inspiration on Biomimicry Architecture - Riri Chairiyah; Ahmad Sarwadi; SyamRachma Marcilia (Journal of Architectural Design and Urbanism, 2018)
Today the advancement of technology and human science has developed rapidly. These developments give a number of technological innovations that were used to solve and facilitate human life. One of the advances in technological innovation is the development of buildings that are designed and established using modern technology. However, the development of these advances, especially man-made buildings, on the contrary, also have a lot of adverse effects on the environment in which humans live. These adverse impacts cause environmental degradation to result in the extinction of a number of natural species around human habitation. These problems are mostly sourced from people who lack environmental awareness. A number of experts to scientists, especially those in charge of development problems, began to look for ways to reduce these adverse impacts. One way that is done especially by architects is to study the process of natural adaptation with its environment which is included in the Biomimicry Architecture. The adaptation process carried out by nature is reflected in how forms, processes and systems that nature uses to respond to its environment. The inspiration was then applied by the architect into the building. Architects in terms of building design must pay attention to three important aspects that exist in the building design process, namely aesthetics, function and strength. However, the aspect of power design in the discussion of biomimicry architecture has a smaller portion than aesthetics and function. While the need for building strength innovations in this regard is very necessary in the building structure against the background of the lack of innovative and environmentally friendly structural design aspects. Based on this problem, this study then used content analysis method with qualitative inductive type. The study was conducted by analyzing written information data that discussed the case of selected buildings, namely The Eden Project Building, The Gherkin Tower and The Eastgate Center. The results of the research are descriptive explanations related to how the adaptive principles applied by the architect into the building use natural inspiration. The benefits of this research are expected to provide an illustration for architects to design buildings that are adaptive to the environment, especially from structural systems and can expand the science of Biomimicry Architecture.